From Family Authority to Individual Autonomy: The Transformation of the Legal Status of Marriage Guardianship in Moroccan Family Law - Sharhan Asad Almawarid; Rodi Wahyudi; Imam Pratama Yendrian (Syakhsiyah Jurnal Hukum Keluarga Islam, 2026)
This article examines the transformation of marriage guardianship (wali nikah) in Moroccan family law from a family-based authority model toward individual legal autonomy. Focusing on the  transformation of legal authority from classical Mālikī jurisprudence to the 2004 Mudawwanah al-Usrah, the study investigates how the position of the guardian shifted from a mandatory pillar of marriage validity into an optional legal institution within contemporary Moroccan family law. Positioned within the discourse of Islamic legal reform, this research argues that the transformation of guardianship in Morocco reflects not merely a legislative change, but a broader epistemological shift in the structure of legal authority in Islamic family law. Using a qualitative library-based method with historical-normative, normative-analytical, and limited maqāṣid al-sharī‘ah approaches, this study analyzes classical fiqh doctrines, hadith traditions, and statutory provisions related to marriage guardianship. The findings reveal that classical Mālikī law constructed guardianship as a representation of patriarchal family authority and social protection, whereas the Mudawwanah reconstructs legal legitimacy around women’s independent legal capacity. This transformation demonstrates a hybrid model of Islamic legal reform that preserves symbolic continuity with fiqh tradition while simultaneously integrating modern principles of gender equality and individual autonomy